2018
DOI: 10.1021/acs.jmedchem.8b01200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dihydrodibenzooxepine Peroxisome Proliferator-Activated Receptor (PPAR) Gamma Ligands of a Novel Binding Mode as Anticancer Agents: Effective Mimicry of Chiral Structures by Olefinic E/Z-Isomers

Abstract: A novel class of PPARγ ligand 1 (EC 50 = 197 nM) with a dibenzoazepin scaffold was identified through highthroughput screening campaign. To avoid the synthetically troublesome chiral center of 1, its conformational analysis using the MacroModel was conducted, focusing on conformational flip of the tricyclic ring and the conformational restriction by the methyl group at the chiral center. On the basis of this analysis, scaffold hopping of dibenzoazepine into dibenzo[b,e]oxepine by replacing the chiral structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…There are only three structural investigations of PGC1a binding to LBDs from two NRs: liver receptor homolog 1 and PPARg (Li et al, 2008;Mays et al, 2017;Yamamoto et al, 2018). How PGC1a interacts with the GR LBD is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are only three structural investigations of PGC1a binding to LBDs from two NRs: liver receptor homolog 1 and PPARg (Li et al, 2008;Mays et al, 2017;Yamamoto et al, 2018). How PGC1a interacts with the GR LBD is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate the chiral center, its bioisosteric scaffolds were designed based on the conformational search of model substrates (R)-2' and (S)-2' (Figure 3). 23 As a result, we found that olefinic E/Z isomers 4 and 5 effectively mimic the chiral structures of (R)-2' and (S)-2', respectively, and discovered dihydrodibenzocycloheptene derivative 3, which has potent PPARγ reporter activity comparable to that of 2.…”
mentioning
confidence: 86%
“…The synthetic compounds were evaluated in vitro via an HEK293 PPARγ reporter gene assay and cell aggregation assay to assess the differentiation-inducing activity against gastric cancer cell line MKN-45, as in our previous study. 23 In addition, compounds were treated with human liver microsome to investigate the metabolic stability.…”
Section: Identification Of 3-fluoro Dibenzooxepine Derivativementioning
confidence: 99%
See 1 more Smart Citation
“…14 However, there are few studies on combining dibenzo[b,f] [1,4]oxazepine and 1,5disubstituted tetrazoles into a bis-heterocyclic system. [15][16][17][18][19] Moreover, dibenzo[b,f] [1,4]oxazepine is an attractive scaffold for de novo drug discovery due to its extended flat aromatic ring system, while having superior drug-like properties (such as cLogP and PSA) compared to its congeners (Figure 1). 20 Mycemycin (C) is an example of an anti-HIV natural product based on the tricyclic ring system.…”
mentioning
confidence: 99%